FRADIR-II: An Improved Framework for Disaster Resilience - Pasic, Alija (2020)
In this paper, we present a framework for disaster resilience, called FRADIR-II, which improves the performance of its previous counterpart. In the novel framework, two different failure models are jointly considered: independent random failures and regional failures that may be used to model the effect of disasters. First, we design an infrastructure against random failures, termed as the spine, which guarantees a certain availability to the working paths. Second, in order to prepare this infrastructure against disasters, we introduce a probabilistic regional failure model, where a modified Euclidean distance of an edge to the epicenter of a disaster is used. The proposed function jointly takes into account the physical length of the edges and their availability, so that a higher/lower availability is reflected in a higher/lower distance from the epicenter. This novel availability-aware disaster failure model generates a failure list which is deemed to be more realistic than previous approaches. Next, a heuristic for link upgrade attempting at the reduction of the likelihood of regional failures disconnecting the network is proposed. Finally, a generalized dedicated protection algorithm is used to route the connection requests, providing protection against the obtained failure list. The experimental results show that FRADIR-II is able to provide disaster resilience even in critical infrastructures.